PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN LENTENG KABUPATEN SUMENEP - jurnalpps pps; Moh. Haris; Nugroho Mardi Wibowo; Muninghar Muninghar (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
The purpose of this study was to examine the effect of leadership style, job satisfaction and organizational commitment either partially or simultaneously on employee performance, and to find out which leadership style, job satisfaction and organizational commitment had a dominant influence on employee performance in Lenteng District, Sumenep Regency. The results showed that either partially or simultaneously, leadership style, job satisfaction and organizational commitment had a significant effect on employee performance at the Lenteng District Office, Sumenep Regency. Organizational commitment has a positive and significant effect on employee performance, leadership style has a positive and significant effect on employee performance at the Lenteng District Office, Sumenep Regency.